SOME REMARKS ON THE LEVEL OF STUDY OF THE GEOLOGICAL AND HYDROGEOLOGICAL STRUCTURE OF FERGANA AREA - Bazarov Abdurasul Abdusamatovich (European Science Publishing, 2023)
The article mainly presents conclusions about the geological and hydrogeological structure of the Fergana region based on the scientific research and opinions of geologists. In addition, information on the deposits of the Fergana region, territorial divisions, Quaternary deposits, and the distribution of underground water, as well as the creation of maps, is presented.
Keywords: Fergana, geological and hydrogeological structure, Central Asia, Oloy ridge, Pleistocene, alluvial layers, young complexes, hydrogeological, drinking water, underground water reserves, fresh water, engineering-geological, tectonic and geomorphological conditions.